EVALUATION OF THE CONTENT OF PHENOLIC COMPOUNDS AND ANTIOXIDANT CAPACITY OF THE ETHANOL EXTRACTS OF THE FRUITS OF AGUAYMANTO (Physalis peruviana L.) FROM DIFFERENT LOCATIONS OF PERU - Jurado Teixeira, Bertha (2016)
The aguaymanto is a native species of the Peruvian highland, which has a tiny fruit that disagrees with its greatness and nutritional therapy. The present investigation had as objetive to assess and compare the total polyphenol content by the Folin-Ciocalteu method and antioxidant capacity of the fruits of Physalis peruviana L., from Huánuco, Junín, Ancash y Cajamarca by the method of the DPPH (1,1-diphenyl-2-picril-hidrazilo). The fruit coming from Huánuco presented a higher content of phenolic compounds expressed as 149.3 ± 1.62 mg/Eq of gallic acid/100g fruit. In addition, greater antioxidant capacity obtaining as inhibitory concentration IC50 1.86 mg/mL, compared with the fruits from Junín, Ancash y Cajamarca; and it would be a good source of consumption in benefit for the health.